A comparison of continuous interscalene block versus general anesthesia alone on the functional outcomes of the patients undergoing arthroscopic rotator cuff repair - Gurger, Murat; Ozer, Ayse Belin (Springernature, 2019)
PurposeThe aim of this prospective and randomized study was to compare the effects of general anesthesia to the combination of general anesthesia and continuous interscalene block on postoperative pain and functional outcomes in patients undergoing arthroscopic rotator cuff repair.MethodsThis study included a total of 85 patients aged 45-74 years, who were scheduled for elective arthroscopic rotator cuff repair. One group consists of patients who underwent only general anesthesia (GA, N=43), and the other group consists of patients who underwent a combination of continuous interscalene brachial plexus block and general anesthesia (CISB+GA, N=42). Pain levels of the patients were evaluated postoperatively by a visual analog scale. Shoulder function was evaluated preoperatively and postoperatively using the Constant score.ResultsPatients in the CISB+GA group had lower postoperative visual analog scores and less additional analgesic needs during the early postoperative period than those in the GA group. Constant scores of the patients in the CISB+GA group at postoperative week 6 were higher than those in the GA group. Evaluation of the functional outcomes at 6 months postoperatively showed that there were no significant differences between the two groups.ConclusionAlthough CISB significantly improved postoperative pain control and early (in the first 6 weeks) functional outcomes following arthroscopic rotator cuff repair, there was no significant difference between the CISB group and CISB+GA group at 6 months.Level of evidenceLevel II, Randomized Controlled Trial, Treatment Study.
Keywords: Interscalene block; Shoulder arthroscopy; Rotator cuff; Functional outcomes